2006
DOI: 10.1017/s1478951506060500
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on spirituality at the end of life: A meta-summary

Abstract: The findings from this meta-summary confirm the fundamental importance of spirituality at the end of life and highlight the shifts in spiritual health that are possible when a terminally ill person is able to do the necessary spiritual work. Existing end-of-life frameworks neglect spiritual work and consequently may be deficient in guiding research. The area of spiritual work is fertile ground for further investigation, especially interventions aimed at improving spiritual health and general quality of life am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(55 citation statements)
references
References 39 publications
(24 reference statements)
0
53
0
2
Order By: Relevance
“…Galek's analysis of the literature revealed seven major constructs, i.e., love and belonging, meaning and purpose, hope and peace, the sacred, appreciation of beauty, morality and ethics, resolution and death [26]. A meta-summary of the qualitative literature on spiritual perspectives of adults extracted thematic pattern of spirituality at the end of life, which were spiritual despair (alienation, loss of self, dissonance), spiritual work (forgiveness, self-exploration, search for balance), and spiritual well-being (connection, self-actualization, consonance) [27].…”
Section: Needs Of Patients With Chronic Diseasesmentioning
confidence: 99%
“…Galek's analysis of the literature revealed seven major constructs, i.e., love and belonging, meaning and purpose, hope and peace, the sacred, appreciation of beauty, morality and ethics, resolution and death [26]. A meta-summary of the qualitative literature on spiritual perspectives of adults extracted thematic pattern of spirituality at the end of life, which were spiritual despair (alienation, loss of self, dissonance), spiritual work (forgiveness, self-exploration, search for balance), and spiritual well-being (connection, self-actualization, consonance) [27].…”
Section: Needs Of Patients With Chronic Diseasesmentioning
confidence: 99%
“…The study covered a 40 year period, and began in 1966 35 . Based on a sample of 11 articles, collectively representing the data of 217 adults, it found that feelings of alienation were an important aspect of spiritual suffering.…”
mentioning
confidence: 99%
“…Nos estudos com metodologia qualitativa foram utilizadas a entrevista semiestruturada (12), a entrevista em profundidade com abordagem fenomenológica (13,14) e o metassumário (15). Na análise temática foram construídos quadros com o resumo dos resultados dos estudos que descreviam as necessidades espirituais, sendo sucessivamente comparados e filtrados de forma a excluir aspectos sem relevância.…”
Section: Métodounclassified